Design parameters for the development of wing test rig for static test experiment / Ramzyzan Ramly … [et_al.] - Ramly, Ramzyzan; Kuntjoro, Wahyu; Wisnoe, Wirachman; M Nasir, Rizal Effendy (Research Management Institute (RMI), 2010)
Airplanes are designed to stay aloft with the help of wings on both sides. In operation at cruising speed, the wings are subjected to load as much as the weight of the whole aircraft. However during manuever, the wings are subjected much higher load and stress and this stress should be sustained by the wings within its limit load without causing permanent deformation to the strucutre. In order to assess how much stress the wings are subjected to, the wings should be tested on ground which is called static test. To proof that a design is good, a numerical analysis should be verified by experimental analysis. The static test can be done in a test rig. The test rig however should be much stronger than the object to be tested. Therefore, the design parameters such as materials selection, design configuration, mounting types, points of load application, boundary conditions are among the parameters to be studied in the development of the test rig. From the research, the simulation was done using CATIA software and the numerical tests was done using ANSYS software. The results from the simulation provided a good picture of the test rig and a prototype was developed using a 40% scale af the actual size being studied.